Low-dose Olaparib improves septic cardiac function by reducing ferroptosis via accelerated mitophagy flux - Ruixue Liu; Fengjuan Li; Shuai Hao; Dongyao Hou; Xue Zeng; He Huang; Gautam Sethi; Jun Guo; Chenyang Duan (Elsevier, 2024)
Sepsis is a dysregulated response to infection that can result in life-threatening organ failure, and septic cardiomyopathy is a serious complication involving ferroptosis. Olaparib, a classic targeted drug used in oncology, has demonstrated potential protective effects against sepsis. However, the exact mechanisms underlying its action remain to be elucidated. In our study, we meticulously screened ferroptosis genes associated with sepsis, and conducted comprehensive functional enrichment analyses to delineate the relationship between ferroptosis and mitochondrial damage. Eight sepsis-characterized ferroptosis genes were identified in sepsis patients, including DPP4, LPIN1, PGD, HP, MAPK14, POR, GCLM, and SLC38A1, which were significantly correlated with mitochondrial quality imbalance. Utilizing DrugBank and molecular docking, we demonstrated a robust interaction of Olaparib with these genes. Lipopolysaccharide (LPS)-stimulated HL-1 cells and monocytes were used to establish an in vitro sepsis model. Additionally, an in vivo model was developed using mice subjected to cecal ligation and perforation (CLP). Intriguingly, low-dose Olaparib (5 mg/kg) effectively targeted and mitigated markers associated with ferroptosis, concurrently improving mitochondrial quality. This led to a marked enhancement in cardiac function and a significant increase in survival rates in septic mice (p < 0.05). The mechanism through which Olaparib ameliorates ferroptosis in cardiac and leukocyte cells post-sepsis is attributed to its facilitation of mitophagy, thus favoring mitochondrial integrity. In conclusion, our findings suggest that low-dose Olaparib can improve mitochondrial quality by accelerating mitophagy flux, consequently inhibiting ferroptosis and preserving cardiac function after sepsis.